2010
DOI: 10.1002/em.20557
|View full text |Cite
|
Sign up to set email alerts
|

Targeting and processing of site‐specific DNA interstrand crosslinks

Abstract: DNA interstrand crosslinks (ICLs) are among the most cytotoxic types of DNA damage, and thus ICL-inducing agents such as cyclophosphamide, melphalan, cisplatin, psoralen and mitomycin C have been used clinically as anti-cancer drugs for decades. ICLs can also be formed endogenously as a consequence of cellular metabolic processes. ICL-inducing agents continue to be among the most effective chemotherapeutic treatments for many cancers; however, treatment with these agents can lead to secondary malignancies, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 154 publications
(232 reference statements)
0
36
0
Order By: Relevance
“…DNA damage induced by cisplatin is repaired by several pathways, including nucleotide excision repair (NER), homologous recombination, and translesion synthesis (32). Suppression of ARID1A as well as ARID1B sensitized cells to cisplatin more significantly than IR but double knockdown of both ARID1 proteins did not increase the cellular sensitivity of single suppression (Fig.…”
Section: Suppression Of Swi/snf Factors Sensitizes Cells To Cisplatinmentioning
confidence: 99%
“…DNA damage induced by cisplatin is repaired by several pathways, including nucleotide excision repair (NER), homologous recombination, and translesion synthesis (32). Suppression of ARID1A as well as ARID1B sensitized cells to cisplatin more significantly than IR but double knockdown of both ARID1 proteins did not increase the cellular sensitivity of single suppression (Fig.…”
Section: Suppression Of Swi/snf Factors Sensitizes Cells To Cisplatinmentioning
confidence: 99%
“…It should be noted that the cells of patients with the syndrome of Fanconi anemia (FA) are characterized by genome instability, and predisposition to malignancy, and by increased sensitivity to IR due to their inability to repair ICL of DNA (Alter, 2002;Kuhnert et al, 2009). ICL initiate the development of DDR with the activation of cell cycle checkpoints, with transmission of the signal along the chain ATM/ATR → Chk1/Chk2 → Cdc25 (A, B, C) → cyclin-CDK (Wu and Vasquez, 2008;Ben-Yehoyada et al, 2009;Vasquez, 2010). It has been also shown that the induction of ICL in DNA is accompanied by formation of γH2AX-foci (Huang et al, 2004;Mogi and Oh, 2006;Mogi et al, 2008).…”
Section: Repair Of Interstrand Cross-links Of Dnamentioning
confidence: 99%
“…Psoralen can form DNA interstrand cross-links upon activation with UVA radiation, and the repair of such cross-links may involve DNA double strand breaks and/or recombination. [12][13][14] Chlorambucil readily forms mono-adducts (as well as some crosslinks) with dsDNA, 15 whereas camptothecin does not react with the DNA strand directly, but rather interfere with topoisomerase I activity by blocking the re-sealing of the DNA, which may eventually result in frank strand breaks. 16 Surprisingly, we find that sequence-targeted PNAs that can react covalently with the DNA helix exhibit a highly inhibitory effect on gene correction in nuclear extract and in a cell culture, extra-chromosomal assay.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%